Production of ZSM-5 zeolites using rotating packed bed: Impact mechanism and process synthesis studies. (23rd November 2021) - Qi, Tingting; Kang, Yingying; Arowo, Moses; Luo, Yong; Chu, Guang-Wen; Zhang, Liangliang; Zou, Hai-Kui; Sun, Baochang; Chen, Jian-Feng
Graphical abstract: Highlights: ZSM-5 zeolite is prepared using rotating packed bed (RPB) in premixing process. Bubble-induced zeolite nucleation mechanism in the RPB is proposed. RPB intensifies the dispersion of aluminosilicate aggregates. As-prepared zeolites exhibit uniform particle sizes and hierarchical structure. Abstract: In this study, hierarchical ZSM-5 zeolites are hydrothermally prepared using rotating packed bed (RPB) in premixing process (gelation stage). The impact mechanisms of RPB on the zeolite growth process are investigated. It is found that the zeolite precursor obtained by RPB contains abundant bubbles, and aluminosilicate aggregates in the precursor are broken and dispersed uniformly, which is beneficial for the uniform and fast growth of zeolite. Additionally, the effects of various RPB-premix process parameters, including rotation speed, premixing time, and liquid feed rate on the particle sizes of ZSM-5 are systematically investigated. The prepared ZSM-5 zeolites by RPB-premix route exhibit smaller particle sizes, narrower particle size distributions, larger specific surface areas, richer pore structure, and more acid amount compared with those by traditional premix treatment. Therefore, this study provides a novel approach for the synthesis of high-performance ZSM-5 zeolites.